PENERAPAN PBL BERBANTUAN KOMIK DENGAN PENDEKATAN CRT UNTUK MENINGKATKAN HASIL BELAJAR IPAS DAN KOLABORASI SDN PANDANWANGI 3 - Shofiyah, Maratus; Thohir, M. Anas; Amzah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the cognitive learning outcomes and collaboration skills of students through the application of the Problem-Based Learning (PBL) model with a Culturally Responsive Teaching (CRT) approach, assisted by comic media integrated in the Learner Worksheet (LKPD). The background of this study is the low achievement of learning outcomes and collaboration skills of fourth-grade students of SDN Pandanwangi 3, Malang City, in IPAS subjects, especially in the subtopic of Social Interaction. This classroom action research (PTK) was conducted in two cycles, each cycle consisting of two meetings. The research subjects were 28 fourth-grade students. Data collection techniques were conducted through learning outcome tests and observation of collaboration skills, while data analysis used a quantitative descriptive approach and a paired t-test statistical test. The results showed that in the pre-cycle, only 17.86% of students reached mastery, increased to 67.86% in cycle I, and reached 85.71% in cycle II. Statistical tests showed a gradual, significant increase. Thus, the implementation of the CRT-based PBL model assisted by comics proved effective in improving learning outcomes and collaboration skills and encouraging meaningful, contextualized learning. It was also rooted in the local culture of students.